Batik: more than just a sarong / Wan Noorli Razali - Razali, Wan Noorli (Academy of Language Studies, 2022)
It is a very rare occasion for us to find Malay women wearing batik sarong when they are going out of the house nowadays. Many new generations find it a hassle to tie batik sarong as they are afraid that it may fall down, a risky situation no one would ever want to experience. Apart from that, some may also feel that it restricts movement especially when we are constantly rushing from one place to another. Today, most women were forced to wear batik sarong either during confinement or when they visit some traditional spa for a massage. Women in the olden days wore batik sarong daily no matter where they go. It was recognized as the appropriate attire to wear when attending special events, not just limited as home-attire. Before we discuss further the multiple ways of wearing it, let us learn the different parts of batik sarong. Generally, batik sarong consists of parts known as kepala kain, badan kain, gunung kain and gigi kain. There are also designs that include apit kiri and apit kanan at each side of the kepala kain. These somehow are absent in the design below.